Measurements of jet multiplicity and jet transverse momentum in multijet events in proton-proton collisions at ?s=13 TeV - Çakır, Affan (SPRINGER, 2023)
Multijet events at large transverse momentum (p(T)) are measured at root s = 13 TeV using data recorded with the CMS detector at the LHC, corresponding to an integrated luminosity of 36.3 fb(-1). The multiplicity of jets with p(T) > 50 GeV that are produced in association with a high-p(T) dijet system is measured in various ranges of the p(T) of the jet with the highest transverse momentum and as a function of the azimuthal angle difference Delta phi(1,2) between the two highest p(T) jets in the dijet system. The differential production cross sections are measured as a function of the transverse momenta of the four highest p(T) jets. The measurements are compared with leading and next-to-leading order matrix element calculations supplemented with simulations of parton shower, hadronization, and multiparton interactions. In addition, the measurements are compared with next-to-leading order matrix element calculations combined with transverse-momentum dependent parton densities and transverse-momentum dependent parton shower.